Immune responses of cattle vaccinated by various routes with Mycobacterium bovis Bacillus Calmette-Guérin (BCG) - Mitchell V. Palmer; Soyoun Hwang; Carly Kanipe; Ellie J. Putz; Luis Guilherme Virgilio Fernandes; Anna Didkowska; Paola M. Boggiatto (BMC Veterinary Research)
Abstract Background Mycobacterium bovis BCG is the human tuberculosis vaccine and is the oldest vaccine still in use today with over 4 billion people vaccinated since 1921. The BCG vaccine has also been investigated experimentally in cattle and wildlife by various routes including oral and parenteral. Thus far, oral vaccination studies of cattle have involved liquid BCG or liquid BCG incorporated into a lipid matrix. Lyophilization is an established technique used for stabilizing bioproducts such as vaccines. Methods In the current study, cattle were vaccinated in two phases. In each phase, cattle were divided into three groups. Group 1 received BCG injected SQ, Group 2 received liquid BCG delivered to the posterior oral cavity, Group 3 orally consumed lyophilized BCG contained within a gelatin capsule placed within a small amount of a commercial alfalfa product. Results No vaccinated cattle were positive by an interferon gamma release assay. All but 4 animals were negative by tuberculin skin testing prior to vaccination: the 4 non-negative animals being categorized as suspects. Sixteen weeks post-vaccination all but 1 animal was negative, it being categorized as a suspect. An in vitro antigen stimulation assay and flow cytometry were used to detect antigen-specific CD4, CD8 and γδ T cell responses following vaccination. Oral vaccination of animals with lyophilized BCG did not result in any increases in the frequency of CD4, CD8 or γδ T cell proliferative or IFN-γ responses at any of the time points analyzed in either phase 1 or 2. In contrast, vaccination with BCG SQ and liquid BCG delivered to the posterior pharynx, resulted in an increase in the frequency of proliferating and IFN-γ-producing CD4 T cells with peak responses at 9–12 weeks post-vaccination. Similar to oral lyophilized BCG vaccinated animals, we did not observe any significant increases in the frequency of CD8 and γδ T cell proliferative and IFN-γ responses following SQ or oral liquid vaccinated animals. Conclusions These data would suggest that vaccination with oral lyophilized BCG does not induce a measurable, antigen-specific cell mediated responses in the periphery, when compared to BCG administered SQ or liquid BCG administered via the oral route. However, vaccination with either SQ or liquid BCG delivered to the posterior pharynx does induce measurable CD4 T cell responses in the periphery.